(untitled) (American Journal of Arts and Human Science, 2025)
Contemporary Visual Masks have often been appreciated for their physical attributes and evaluated through the lens of established elements and principles of artistic practice and analysis. Seldom are they considered for their semiotic qualities. It is imperative that masks, which were originally not made for their aesthetic appeal but rather functional attributes, be looked at both aesthetically and semiologically. The aim of this study was to employ the technique of assemblage and construction in sculpture to combine elements of various signs to form new composite symbols. In addition, the study was intended to explore semiology in visual perception through the masks produced as graphic communication. The study employed a qualitative research paradigm, utilizing a descriptive research design to provide a detailed description of selected masks produced by the researcher. The researcher’s conceptual framework involved personal experiential knowledge, existing theory and research, and exploratory research, making the researcher the principal instrument for the research. The findings discussed the general characteristics of the masks, including their size, names, materials used, and the concepts behind their production. The study recommends encouraging the study and utilization of semiotics in art institutions and universities to appreciate art better. This approach would complement aesthetics and enhance the overall experience and appreciation of visual masks.